Should platinum-based chemotherapy be preferred for germline BReast CAncer genes (BRCA) 1 and 2-mutated pancreatic ductal adenocarcinoma (PDAC) patients? A systematic review and meta-analysis. (November 2019) - Rebelatto, Taiane F.; Falavigna, Maicon; Pozzari, Marta; Spada, Francesca; Cella, Chiara A.; Laffi, Alice; Pellicori, Stefania; Fazio, Nicola
Highlights: Germline BRCA mutated PDAC patients account for 5–20% of cases. Our study confirmed the hypothesis that PtCh is more effective in these patients. However this was based on a very low level of evidence. Thus this hypothesis should be verified with a randomized clinical trial. Abstract: Background: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal cancers worldwide. Recent studies have shown that 4–20% of patients with PDAC have a germline BReast CAncer (g BRCA ) genes 1 and 2 mutation (m). Because homologous recombination is impaired in patients with g BRCA m, some reports suggested that these tumors may be more sensitive to platinum compounds. Therefore, this systematic review and meta-analysis focused on benefit of patients with g BRCA m receiving a platinum-based chemotherapy (PtCh) compared with those treated with a non-platinum-based chemotherapy (NPtCh). Material and methods: The following electronic databases were searched from inception to May 12, 2018: PubMed (MEDLINE), EMBASE, and Cochrane Library. Abstracts from conferences were also reviewed for inclusion. Cohort, case-control and randomized studies of patients with PDAC and g BRCA m were eligible for inclusion if they provided data to compare patients receiving PtCh vs NPtCh. The primary endpoint was overall survival (OS) in the PtCh group vs the NPtCh group in patients with clinical stage III (locally advanced) or IV (metastatic) (CS III-IV) PDAC. Results: Of 112 studies identified, 6 were included (total of 108 patients); of these, 4 provided sufficient data for meta-analysis. Half of the patients were males, with a mean age ranging from 58 to 63 years. The OS in the 85 patients with CS III-IV PDAC was higher in the PtCh group (23.7 vs 12.2 months; mean difference of 10.21 months, 95% confidence interval [CI] 5.05–15.37; P < 0.001; very low quality of evidence). PtCh was associated with a lower mortality (62.3 vs 87.5%; relative risk of 0.80, 95%CI 0.66–0.97; P = 0.021; very low quality of evidence). Conclusion: Our study confirmed the hypothesis that patients with CS III-IV g BRCA m preferably benefit from a PtCh compared with NPtCh. However the very low quality of evidence should induce to be careful about the risk of potential biases. The generated hypothesis should be prospectively investigated in homogenous clinical settings.